Geographical and linguistic structure in the people of Kenya demonstrated using 21 autosomal STRs. (July 2021) - Muinde, Jane Mbithe; Chandra Bhanu, Devi R.; Neumann, Rita; Oduor, Richard Okoth; Kanja, Wangu; Kimani, Joseph Kagunda; Mutugi, Marion W.; Smith, Lisa; Jobling, Mark A.; Wetton, Jon H.
Abstract: Kenya is a diverse and populous nation that employs DNA evidence in its criminal justice system, and therefore requires reliable information on autosomal STR allele frequency variation across the country and in its many ethnic groups. In order to provide reference data and to assess population structure, we analysed the 21 autosomal STRs in the GlobalFiler multiplex in a sample of 510 indigenous Kenyans representing the country's eight former provinces, 43 of its 47 counties, three main linguistic families and all 29 ethnic groups that each comprise >0.5% of the 2019 census population. The indigenous population originated from successive migrations of Cushitic, Nilotic and Bantu speaking groups who settled in regions that suited their distinctive sustenance lifestyles. Consequently, they now largely reside in a patchwork of communities with strong associations with particular counties and provinces and limited degrees of inter-group marriage, as shown by DNA donors' ancestry details. We found significant genetic differentiation between the three Nilotic language sub-families, with Western Nilotes (the Luo ethnic group) showing greater similarity to the Bantu than the Southern and Eastern Nilotes which themselves showed closer affinity to the Cushitic speakers. This concurs with previous genetic, linguistic and social studies. Comparisons with other African populations also showed that linguistic affiliation is a stronger factor than geography. This study revealed several rare off-ladder alleles whose structure was determined by Sanger sequencing. Among the unusual features that could affect profile interpretation were a deletion of Amelogenin Y but no other forensic marker (autosomal or Y-chromosomal), a triallelic pattern at TPOX and an extremely short SE33 allele falling within the expected size range of D7S820. Compared with the currently implemented Identifiler multiplex, Random Match Probabilities decreased from 6.4 × 10 –19 to 3.9 × 10 –27 . The appreciation of local population structure provided by the geographically and ethnically representative sample in this study highlights the structured genetic landscape of Kenya. Highlights: GlobalFiler (21-STR) genotypes reported for 510 ethnolinguistically-defined Kenyan males. Significant genetic differentiation between three Nilotic language subfamilies. Linguistic affiliation more important than geography in structuring population. Rare and off-ladder alleles sequenced. Random match probabilities increase by >6 orders of magnitude compared to Identifiler.